Characterization of methane hydrate extraction influenced by hydraulic fractures using a coupled thermo-hydro-mechanical-chemical model - Sun, Hao; Xu, Xiangyu; Jia, Chao (Frontiers in Earth Science, 2024)
The low permeability of the methane hydrate-bearing sediment limits the methane gas extraction. To enhance methane hydrate extraction, hydraulic fracturing can be a promising approach to improve the hydrate reservoir permeability by creating a fracture network in the reservoir. In this study, a coupled thermo-hydro-mechanical-chemical mathematical model and its numerical implementation based on finite element technology are introduced to analyze the methane hydrate extraction through fractured methane hydrate-bearing sediment considering methane hydrates dissociation, gas-water two-phase flow, heat transfer, dynamic changes of the sediment permeability, and deformation of both sediment matrix and fractures as well as capturing the interplay between them. The coupled thermo-hydro-mechanical-chemical numerical model is verified by reproducing a methane hydrates dissociation laboratory test. Finally, we conduct a series of simulations for the methane gas depressurization extraction through the sediments with the DFNs assigned as diverse geometrical characteristics. The influence of hydraulic fracture network geometrical and hydraulic characteristics on methane hydrate extraction are discussed. The results can offer a reference for enhancing the methane hydrate extraction efficiency.